Active galactic nuclei and gravitational redshifts - Padilla, Nelson David (2024)
Context. Gravitational redshift is a classical effect of General Relativity. It has been measured in stars, quasars, and clusters of galaxies. Aims. We identify the signature of gravitational redshift in the emission lines of active galaxies that is caused by supermassive black holes and compare this signature to what is found for inactive galaxies. Methods. Using the virial theorem, we estimated gravitational redshifts for quasars from the 14th data release (DR14) of the Sloan Digital Sky Survey (SDSS) and compared them with measured gravitational redshifts from the difference between the redshifts of emission lines of Sydney Australian Astronomical Observatory Multi-object Integral Field (SAMI) galaxies in the central and outer annuli of their integral field spectra. Results. Firstly, from the full width at half maximum of Hβ lines of 57 Seyfert type I galaxies of the active galactic nucleus (AGN) Black Hole Mass Database, we derive a median gravitational redshift zg = 1.18 × 10‑4. Expanding this analysis to 86 755 quasars from DR14 of SDSS, we have a median value zg = 1.52 × 10‑4. Then, by comparing the redshifts of 34 lines measured in the central and outer regions of low-ionization nuclear emission-line region galaxies in the SAMI survey, we obtain zg = (0.68 ± 0.09)×10‑4, which increases to zg = (1.0 ± 0.1)×10‑4 for the Hα and Hβ lines. These numbers are compatible with central black holes of ∼109 solar masses and broad line regions of ∼1 pc. For non-AGN galaxies, the gravitational redshift is compatible with zero.